Desain Soal Numerasi Konteks Saintifik dengan Integrasi Konsep Maritim - Fachrudin, Achmad; Novitasari, Novitasari; Rahmawati, Tanti Diyah (Universitas Negeri Surabaya, 2025)
As a maritime nation with significant marine potential, integrating maritime contexts into secondary education in Indonesia is essential for preparing students to understand mathematical concepts and their applications in various maritime professions. To support this goal, we developed scietific numeracy tasks by integrating maritime concepts. We designed the tasks based on a literature review related to maritime concepts and referred to the PISA framework, which was then realized in the form of a maritime numeracy conceptual framework. This framework consists of four main subcontexts: navigation, marine engineering, oceanography, and maritime economics. We developed tasks for each subcontexts, which were evaluated by three experts. The experts validated based on relevance of the maritime context, involvement of maritime concepts, suitability in measuring numeracy, and quality of the tasks from pedagogical aspect. The evaluation results showed that the quality of the tasks was in the very good category in all aspects, with a moderate and good level of agreement among the experts, indicated by the interclass correlation coefficient score of 0.538. This research is expected to contribute to the innovation of numeracy task design with scientific contexts that specifically accommodate maritime concepts and support efforts to improve students’ numeracy in Indonesia.